2002
DOI: 10.1083/jcb.200201025
|View full text |Cite
|
Sign up to set email alerts
|

Np95 is regulated by E1A during mitotic reactivation of terminally differentiated cells and is essential for S phase entry

Abstract: Terminal differentiation exerts a remarkably tight control on cell proliferation. However, the oncogenic products of DNA tumor viruses, such as adenovirus E1A, can force postmitotic cells to proliferate, thus representing a powerful tool to study progression into S phase. In this study, we identified the gene encoding Np95, a murine nuclear phosphoprotein, as an early target of E1A-induced transcriptional events. In terminally differentiated (TD) cells, the activation of Np95 was specifically induced by E1A, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 30 publications
(50 reference statements)
6
82
0
Order By: Relevance
“…Loss of UHRF1 function abrogates S phase entry, and its overexpression shortens the cell cycle (22)(23)(24)46), in agreement with our finding that uhrf1 is up-regulated during regeneration in parallel with ccna2 and is required for hepatocyte proliferation in vivo. We postulate that this role is liver specific in adults, because fin regeneration (SI Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Loss of UHRF1 function abrogates S phase entry, and its overexpression shortens the cell cycle (22)(23)(24)46), in agreement with our finding that uhrf1 is up-regulated during regeneration in parallel with ccna2 and is required for hepatocyte proliferation in vivo. We postulate that this role is liver specific in adults, because fin regeneration (SI Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, several stable transformants from HEK293 and WI-38 cells that had been transfected with antisense human NP95 cDNA were more sensitive to X rays, UV light and hydroxyurea than the corresponding parental cells [12] . Additionally, there was no significant redistribution of UHRF1 foci shortly after DNA damage by γ-irradiation, but nodular UHRF1 foci characteristically seen in the G 2 phase were also detected in G 2 -arrested cells following γ-irradiation [6] . These results indicate that UHRF1 may play an important role in the regulation of radiosensitivity.…”
Section: Introductionmentioning
confidence: 96%
“…Mouse UHRF1 is strongly expressed in the testis, spleen, thymus, and lung tissue, but not in the brain, liver, or skeletal muscles [4] . Although the biological functions of UHRF1 are unknown, previous studies have suggested that (i) UHRF1 does not have a direct role in DNA replication as part of the DNA synthesizing machinery, like PCNA, but is presumably involved in other DNA replication-linked nuclear events [5] ; (ii) UHRF1 may be a growth-regulated gene because its expression is regulated during the cell cycle, required for the G 1 /S transition, and specifically induced by E1A, which can force post-mitotic cells to proliferate, and it is a chromatin-associated ubiquitin ligase [6,7] ; (iii) UHRF1 mRNA levels are also increased in transformed BALB/3T3 cells, suggesting that it may participate in the maintenance of the transformed phenotype [8] ; (iv) UHRF1 might help recruit DNA-cytosine-5-methyltransferase 1 (DNMT1) to hemimethylated DNA to facilitate faithful maintenance of DNA methylation [9,10] ; and (v) mouse Np95-null (Np95 -/-) embryonic stem cells are more sensitive to X rays, UV light, N-methyl-N′-nitro-N-nitrosoguanidine, and hydroxyu-rea than wild-type (Np95 +/+ ) or Np95 +/− embryonic stem cells [11] . Furthermore, several stable transformants from HEK293 and WI-38 cells that had been transfected with antisense human NP95 cDNA were more sensitive to X rays, UV light and hydroxyurea than the corresponding parental cells [12] .…”
Section: Introductionmentioning
confidence: 99%
“…ICBP90 and its mouse orthologue Np95 are required for cell proliferation particularly for the G 1 /S transition (Bonapace et al, 2002;Arima et al, 2004;Jeanblanc et al, 2005;Jenkins et al, 2005). Considering that ICBP90 interacts with the RB1 gene product (Jeanblanc et al, 2005) which cooperates with the heterochromatin protein 1 and the histone methylase SUV39H1 to repress the cyclin E promoter (Nielsen et al, 2001), ICBP90 is likely to play a role in gene silencing.…”
Section: Ink4amentioning
confidence: 99%